Pathogenic and Epiphenomenal Anti-DNA Antibodies in SLE. (10th June 2010) - Pavlovic, Mirjana; Kats, Anna; Cavallo, Michelle; Chen, Ran; Hartmann, James X.; Shoenfeld, Yehuda
Abstract : The discoveries of natural and the development of manufactured highly efficient catalytic antibodies (abzymes) opens the door to many practical applications. One of the most fascinating is the use of such antibodies in human therapy and prevention (vaccination), of cancer, AIDS, autoimmune diseases. A special entity of naturally occurring DNA hydrolytic anti-DNA antibodies is emerging within past decades linked to autoimmune and lymphoproliferative disorders, such as systemic lupus erythematosus (SLE), multiple sclerosis (MS), Sjogren Syndrome (SS), B - Chronic lymphocytic leucosis (B-CLL), and Multiple Myeloma (MM). The origin of the antibodies is unknown. The underlying mechanisms of these activities are suggested to be penetration into the living cells and translocation in the nucleus, with recognition of the specific binding sites at particular (ss or ds) DNA. There are controversies in the literature whether hydrolysis is a sequence-specific event. The interplay between anti-DNA antibodies and DNA is not yet elucidated. This molecular "twist" also suggests that anti-DNA antibodies with DNA hydrolytic capacity could be the organism's immune response to a microbial attack, with microbial DNA, or specific genes within microbial DNA sequence, as a target for neutralization. The catalytic antibody-based approach can become a key tool in selective chemotherapeutic strategies.